Menggali Pengertian, Sejarah, dan Manfaat dari Mempelajari ‘Ulumul Qur'an - Mutia Rahmah; Annisa Maulidya (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to examine the definition, historical development, and scope of 'Ulum al-Qur'an. The findings reveal that 'Ulum al-Qur'an is a discipline that thoroughly explores various aspects related to the Qur'an, including its history, methods of interpretation, and relevant principles. This field plays a fundamental role in comprehensively understanding the Qur'an, as the holy scripture serves as the primary guide for Muslims and the main source of Islamic teachings. A deep understanding of the Qur'an requires mastery of 'Ulum al-Qur'an, which encompasses essential aspects of interpretation, including the requirements and appropriate methods. Through studying 'Ulum al-Qur'an, readers are expected to accurately comprehend the words of Allah through tafsir, recognize correct interpretive methods, and understand the prerequisites necessary for the process. This study emphasizes the importance of mastering 'Ulum al-Qur'an as a key to comprehensively understanding Islamic teachings.